2005
DOI: 10.1074/jbc.m500358200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Salmonella-containing Vacuole with the Endocytic Recycling System

Abstract: Upon entry of the pathogen Salmonella enterica serovar Typhimurium into host cells, the majority of bacteria reside in a membrane-bound compartment called the Salmonella-containing vacuole (SCV). Previous studies have established that the SCV transiently interacts with early endosomes but only acquires a subset of late endosomal/lysosomal proteins. However, the complete set of interactions between the SCV and the endocytic machinery has yet to be characterized. In this study, we have shown that four characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 64 publications
1
60
1
Order By: Relevance
“…Previous studies have shown that intracellular pathogens either mimic or target these proteins to establish their niche in the host cells (20,21,24). Similarly, maturation of SCP also depends on the sequential removal and recruitment of different Rabs and syntaxins (2,3,15,19,28). In this study, we have determined the recruitment of different syntaxins on SCP at various stages of their maturation in macrophages and have shown that SCP specifically recruit higher amounts of Syntaxin6 after 90 min of internalization than at 5 min of internalization.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that intracellular pathogens either mimic or target these proteins to establish their niche in the host cells (20,21,24). Similarly, maturation of SCP also depends on the sequential removal and recruitment of different Rabs and syntaxins (2,3,15,19,28). In this study, we have determined the recruitment of different syntaxins on SCP at various stages of their maturation in macrophages and have shown that SCP specifically recruit higher amounts of Syntaxin6 after 90 min of internalization than at 5 min of internalization.…”
Section: Discussionmentioning
confidence: 95%
“…By far the best-documented aspect of SCV biogenesis is the sequential delivery of endolysosomal membrane proteins that defines the conversion of early to intermediate SCVs. Thus the early SCV membrane is highly enriched in early endosome membrane markers, including EEA1, Rab5 and transferrin receptor, which are replaced within 20-40 min with late endosomal/lysosomal markers including Lamps and vATPase [7,8]. This change in membrane content is accompanied by a decrease in the luminal pH (pH scv ) to <4.5 [9,10] and redistribution of the SCV to a predominantly juxtanuclear position near the microtubule organizing center (MTOC) [11].…”
Section: The Salmonella-containing Vacuolementioning
confidence: 99%
“…In the first step (0 to 15 min p.i. ), the SCV interacts with early endosomes and acquires the markers Rab4, Rab5, and EEA1 (175,181). The role of Rab5 in SCV biogenesis was explored by Baldeon and colleagues (12).…”
Section: Salmonella Enterica Serovar Typhimuriummentioning
confidence: 99%
“…For example, SCVs recruit Rab11 and syntaxin 13, with a maximal association at 60 min p.i. (175). Using a dominant negative approach, we determined that Rab11 regulates the recycling of CD44 from SCVs but had no effect on major histocompatibility complex class I recycling.…”
Section: Salmonella Enterica Serovar Typhimuriummentioning
confidence: 99%
See 1 more Smart Citation